An Analysis of the Islamization of knowledge project International Islamic University Malaysia as a case study - Demirel, Serdar (2011)
Islamization of knowledge is a project to reorient systematically and restructure the entire field of human knowledge in accordance with a new set of criteria and categories, derived from, and based on the Islamic worldview. This paper aims to provide further suggestions to contribute to the the project.